EXAMINING STUDENTS' BEHAVIORAL USE OF CAMPUS JOURNALS WITH THE TECHNOLOGY ACCEPTANCE MODEL APPROACH - Agus Pratama W; Asrul Sani; Siti Aisyah; Merliani Ivone S; Agus Budiyantara (Kresnamedia Publisher, 2022)
Understudy conduct is an action completed by understudies for every person. Students who visit campus journal websites are essential in terms of journal accreditation aspects, where this is a benchmark for increasing the journal's potential as a reference. However, some factors influence it where the frequency of students visiting campus journal websites is not as expected in exploring journals, and the enthusiasm of students to download articles is still below the desired expectations. It causes the potential for the journal to obtain national accreditation at a small percentage, and students may think that there are very few reference sources for journals, so it is less attractive on the campus journal website system. Data collection methods were used in this study, such as interviews, literature study, and questionnaires. Meanwhile, evaluate the campus journal website system on student behavior using the Technology Acceptance Model (TAM) with four variables: perceived ease of use, usefulness, attitude toward using, and behavioral intention to use. This method makes the user feel it is easier to access the campus journal website; then, the user feels the campus journal website can provide benefits and usability. The user has a great curiosity about accessing the campus journal, and finally, the user wants to access the website and take the initiative to influence. other users in to access the same